Expaining model of affecting factors on e-learning effectiveness in post graduate courses - Mahdi Kheyrandish (Journal of Information Technology Management)
The quality of learning is one of the basic elements in every society to reach achievements. This subject has more importance on e-learning. Accordingly, the present study explains the affecting factors on e-learning programs’ effectiveness. Regarding the aims, the present research is descriptive and regarding the application is practical. Data collection method is research made questioner. In order to reach this aim, 106 samples including deans, experts and lecturers of e-learning programs have been randomly chosen and by application of partial least square method five different factors affecting the effectiveness of e-leaning including university-related, student features and characteristics, lecturer’s features and characteristics, learning conditions and environmental factors have been determined. Yet, the consequences of the study revealed that the learning conditions factor and the university-related factor have respectively the most and the least effects on the effectiveness of e-learning.